Information literacy skills of primary school teachers in Lagos Mainland Local Government Area, Lagos state, Nigeria (2019)
The study investigated the Information Literacy Skills (ILS) of4 76 teachers in 5 7primary schools in Lagos Mainland Local Government using a descriptive survey. A stratified random sampling was used to select a sample of 173 teachers and a questionnaire was used to collect data which was analysed using frequency distribution. The findings revealed the major information needs oj primary school teachers as academic (71.1%) and economic (67.6%). The ILS of the teachers was high (Mean — 37.6) and the major methods of ILS acquisition were: training programmes (86.1 %), library user education (81.6%), use of school library’ media centre (73.9%) and engaging in information search process (72.3%). Primary school teachers possessed high ILS and this can be improved upon through user education by school librarians and professional development.